The UK Foundation Programme for newly qualified doctors: a SWOT analysis - David Stephen Lawrence; Christopher Gareth Williams (Sociedade Brasileira de Medicina de Família e Comunidade, 2014)
Introduction: After completing a five year undergraduate degree, all newly qualified doctors in the United Kingdom undertake a two-year Foundation Programme which aims to provide them with the necessary experience, supervision and guidance to prepare them for a career in clinical medicine. Foundation Doctors are paid members of the team and undertake a variety of clinical rotations with supervision from senior colleagues, a process that is regulated by a UK Foundation Programme Office. Objective: This paper aims to provide a reflective analysis of this programme to greater inform the international audience. Methods: A critical reflective analysis utilising the SWOT format (Strength, Weaknesses, Opportunities and Threats), conducted by two Foundation Doctors working in the UK. Results and Discussion: We identified a well-established programme which enabled graduates to gain a broad range of clinical experience as a paid doctor but one with considerable variation at both individual and group level. Long-standing shortcomings of being a junior-doctor including long hours and excessive paperwork were still prevalent. We highlighted potential opportunities and threats within the current system, some of which were dependent upon larger political systems governing the NHS in the UK. Conclusion: The Foundation Programme is a robust approach to the training and development of early career doctors. Further research and a deeper international dialogue on the best-practice in this field is needed.